Re-evaluation of Laparoscopic Hepatic Subcapsular Spider-Like Telangiectasis Sign: A Highly Accurate Method to Diagnose Biliary Atresia in Infants - Li, Yibo; Rong, Liying; Tang, Jingfeng; Niu, Huizhong; Jin, Zhu; Zhou, Yun; Cao, Guoqing; Zhang, Xi; Chi, Shuiqing; Tang, Shaotao (Frontiers in Pediatrics, 2022)
Objective: Operative cholangiography, the gold standard for the diagnosis of biliary atresia (BA), is challenged due to the increasingly studies of misdiagnosis. Previous study has shown that the laparoscopic hepatic subcapsular spider-like telangiectasis (HSST) sign was accurate for diagnosing BA. This study aims to compare the performance of HSST sign with cholangiography in the identification of BA. Methods: We prospectively screened consecutive infants with cholestasis who underwent laparoscopic exploration in this multicenter study. Demographics, intraoperative findings (videos and images), and outcomes were retrospectively analyzed. The data of HSST sign and cholangiography were compared according to the final diagnosis. Then, the diagnostic accuracy of the BA using HSST sign and cholangiography was validated in other independent cohort. Results: A total of 2216 patients were enrolled in this study. The sensitivity and negative predictive value were both 100% for diagnosing BA based on the HSST sign and cholangiography. The specificity, negative predictive value, and accuracy of the HSST sign (97.2%, 99.2%, 99.3%) in discriminating BA were significantly higher than operative cholangiography (81.6%, 94.9%, 95.8%; p<0.001). Moreover, to realize the early diagnosis of BA, the accuracy of the HSST sign in identifying BA was better than cholangiography in the subgroup of neonates (98.7% vs. 95.0%; p=0.032). Interestingly, 92 non-BA patients without HSST sign had positive cholangiography. Among them, 28 infants had negative cholangiography when the common bile duct was compressed and 39 patients displayed visible bile ducts due to repeated postoperative biliary irrigation. The other 25 patients (18 with Alagille syndrome, 5 with progressive familial intrahepatic cholestasis, and 2 with neonatal hepatitis syndrome) had consistently positive cholangiography. In the independent validation cohort, the diagnostic accuracy of HSST sign (99.2%) was higher than cholangiography (95.0%, p=0.012). Conclusions: The laparoscopic HSST sign is superior to cholangiography in diagnosis of BA in infants with cholestasis, and also has advantages in early diagnosis. This method is expected to become a novel shift for diagnosing BA during ongoing laparoscopy.